2001
DOI: 10.1074/jbc.m006564200
|View full text |Cite
|
Sign up to set email alerts
|

PTHrP Modulates Chondrocyte Differentiation through AP-1 and CREB Signaling

Abstract: During the process of differentiation, chondrocytes integrate a complex array of signals from local or systemic factors like parathyroid hormone-related peptide (PTHrP), Indian hedgehog, bone morphogenetic proteins and transforming growth factor ␤. While PTHrP is known to be a critical regulator of chondrocyte proliferation and differentiation, the signaling pathways through which this factor acts remain to be elucidated. Here we show that both cAMP response element-binding protein (CREB) and AP-1 activation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
84
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(94 citation statements)
references
References 58 publications
9
84
1
Order By: Relevance
“…PKA phosphorylates and activates CREB, and PTH activates AP1 family members such as Fos/Jun. Although these PKAassociated molecules are involved in bone development, recent evidence suggests a role for AP1 and CREB in differentiation rather than in proliferation (59). Our data indicate that the inhibition of PKA does not block cAMP-induced mitogenic action in cells of bone origin, regardless of whether the cells express or lack 95-kDa B-Raf.…”
Section: Dual Functionality Of Pth On Cell Proliferation 22196mentioning
confidence: 49%
“…PKA phosphorylates and activates CREB, and PTH activates AP1 family members such as Fos/Jun. Although these PKAassociated molecules are involved in bone development, recent evidence suggests a role for AP1 and CREB in differentiation rather than in proliferation (59). Our data indicate that the inhibition of PKA does not block cAMP-induced mitogenic action in cells of bone origin, regardless of whether the cells express or lack 95-kDa B-Raf.…”
Section: Dual Functionality Of Pth On Cell Proliferation 22196mentioning
confidence: 49%
“…We and others have shown that PTH/PTHrP signaling stimulates cyclin D1 transcription in chondrocytes (55)(56)(57). Recent work has identified a Rho-specific activator, the guanine nucleotide exchange factor CDEP, as a target of PTH in chondrocytes (58, 59).…”
Section: Resultsmentioning
confidence: 99%
“…Ectopic expression of Fos in developing chicken limb buds by retroviral microinjection causes truncation of the cartilage in the long bones of the injected leg; this is due to chondrodysplasia caused by severely retarded differentiation of the proliferating chondrocytes into mature chondrocytes, hypertrophy of chondrocytes, and delays in precartilagenous condensation (11). AP-1 also plays an essential role in the regulation of chondrocyte differentiation by parathyroid hormone-related protein through induction of c-Fos protein expression (12). Genetic studies in mice have provided compelling evidence for the role of AP-1 family members in skeletal development in vivo.…”
mentioning
confidence: 99%